Probing Charge Transfer and Hot Carrier Dynamics in Organic Solar Cells with Terahertz Spectroscopy - Cunningham, Paul D. (Proc SPIE Int Soc Opt Eng, 2016)
Time-resolved terahertz spectroscopy (TRTS) was used to explore charge generation, transfer, and the role of hot carriers in organic solar cell materials. Two model molecular photovoltaic systems were investigated: with zinc phthalocyanine (ZnPc) or alpha-sexathiophene (α-6T) as the electron donors and buckminsterfullerene (C(60)) as the electron acceptor. TRTS provides charge carrier conductivity dynamics comprised of changes in both population and mobility. By using time-resolved optical spectroscopy in conjunction with TRTS, these two contributions can be disentangled. The sub-picosecond photo-induced conductivity decay dynamics of C(60) were revealed to be caused by auto-ionization: the intrinsic process by which charge is generated in molecular solids. In donor-acceptor blends, the long-lived photo-induced conductivity is used for weight fraction optimization of the constituents. In nanoscale multilayer films, the photo-induced conductivity identifies optimal layer thicknesses. In films of ZnPc/C(60), electron transfer from ZnPc yields hot charges that localize and become less mobile as they thermalize. Excitation of high-lying Franck Condon states in C(60) followed by hole-transfer to ZnPc similarly produces hot charge carriers that self-localize; charge transfer clearly precedes carrier cooling. This picture is contrasted to charge transfer in α-6T/C(60), where hole transfer takes place from a thermalized state and produces equilibrium carriers that do not show characteristic signs of cooling and self-localization. These results illustrate the value of terahertz spectroscopic methods for probing charge transfer reactions.